The Impact of Carbon Emission Disclosure On Firm Value With Sustainability Performance As A Mediating Variable: Evidence From Palm Oil and Mining Companies In Indonesia - Harnida, Muthia; Bulkia, Sri; Nurhayati, Netty; Anshory, Kemas; Aulia Tambang, Pasha (Publisher Cv. Inara, 2025)
This study aims to analyze the impact of carbon emission disclosure on firm value, with sustainability performance as a mediating variable. This study focuses on palm oil and mining companies listed on the Indonesia Stock Exchange (IDX) with 105 data points for the period 2019–2023. Carbon emission disclosure is a form of corporate transparency in managing environmental impacts and is increasingly a major concern for stakeholders, particularly investors. However, the direct relationship between carbon emission disclosure and firm value remains a gap in various previous studies. This study used a panel data regression with a fixed effects model equipped with robust standard errors (clustered by company). Carbon emission disclosure is measured using the Global Reporting Initiative (GRI) 305: Emissions index, Sustainability performance with Environmental, Social, and Governance (ESG) score as the proxy for sustainability performance, and firm value by the Tobin's Q ratio. The results indicate that carbon emission disclosure has a direct effect on firm value. However, ESG in this study does not mediate the relationship between carbon emission disclosure and firm value. The implications of this research are expected to be a reference for companies in increasing sustainability transparency and for regulators in formulating policies for carbon emission disclosure and its incentive mechanism.